High strength geopolymer binder based on waste-glass powder - Vafaei, Mostafa; Allahverdi, Ali (Advanced powder technology : the international journal of the Society of Powder Technology, Japan, 2017)
[Display omitted] •Waste-glass powder and CACs were used to produce geopolymer binder.•Inclusion of CACs resulted in a denser microstructure and enhanced strength.•Hydrothermally cured mortars of optimum composition exhibited strengths up to 87MPa. This paper presents a study on the synthesis of geopolymers based on alkaline activation of waste-glass powder using aqueous solutions of sodium hydroxide and sodium silicate with different Na2O contents as alkali activators. Three types of calcium aluminate cements were also incorporated into the dry binder at levels up to 24% by weight in order to modify the chemical composition of the geopolymer source materials. The prepared mortars were tested for workability, setting time, compressive strength, free-alkali content and tendency towards efflorescence formation. FTIR and SEM analyses were also performed to characterize the morphology and structure of the produced geopolymer. The optimized geopolymer mortar exhibited a remarkable maximum compressive strength of 87MPa. The results showed that inclusion of calcium aluminate cements in the silica-rich waste-glass powder leads to release high amounts of reactive alumina into aluminosilicate gels, improving the geopolymerization reactions and resulting in the formation of a more cross-linked network that exhibits higher compressive strength. High alumina cement Secar 71 showed the greatest effect in strength enhancement due to the higher amount of reactive alumina releasing into the reaction medium. The findings demonstrate a new potential of value-added reuse application for waste-glass powder by adding a suitable amount of materials that are rich in reactive alumina.